2018
DOI: 10.1016/j.neuron.2018.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Astrocyte Calcium Signaling In Vivo Alters Striatal Microcircuits and Causes Repetitive Behavior

Abstract: Astrocytes tile the central nervous system, but their functions in neural microcircuits in vivo and their roles in mammalian behavior remain incompletely defined. We used two-photon laser scanning microscopy, electrophysiology, MINIscopes, RNA-seq, and a genetic approach to explore the effects of reduced striatal astrocyte Ca signaling in vivo. In wild-type mice, reducing striatal astrocyte Ca-dependent signaling increased repetitive self-grooming behaviors by altering medium spiny neuron (MSN) activity. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
277
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 287 publications
(305 citation statements)
references
References 61 publications
9
277
0
Order By: Relevance
“…Therefore, methods with cellular resolution like electrophysiology combined with fluorescent detection of markers, multidimensional cytometry, and two‐photon imaging with functional sensors are methods of choice to establish how specific types of reactive astrocytes function. Several elegant studies recently succeeded in providing new insight into the complexity of astrocyte functions in the normal brain (Bindocci et al, ; Chung et al, ; Martin, Bajo‐Graneras, Moratalla, Perea, & Araque, ; Nimmerjahn & Bergles, ) and in disease (Bardehle et al, ; Delekate et al, ; John Lin et al, ; Yu et al, ). Future studies will need to implement such refined methods in relevant disease models, to study reactive astrocyte responses at the single‐cell level.…”
Section: Which New Approaches and Tools Will Move The Field Forward?mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, methods with cellular resolution like electrophysiology combined with fluorescent detection of markers, multidimensional cytometry, and two‐photon imaging with functional sensors are methods of choice to establish how specific types of reactive astrocytes function. Several elegant studies recently succeeded in providing new insight into the complexity of astrocyte functions in the normal brain (Bindocci et al, ; Chung et al, ; Martin, Bajo‐Graneras, Moratalla, Perea, & Araque, ; Nimmerjahn & Bergles, ) and in disease (Bardehle et al, ; Delekate et al, ; John Lin et al, ; Yu et al, ). Future studies will need to implement such refined methods in relevant disease models, to study reactive astrocyte responses at the single‐cell level.…”
Section: Which New Approaches and Tools Will Move The Field Forward?mentioning
confidence: 99%
“…Several elegant studies recently succeeded in providing new insight into the complexity of astrocyte functions in the normal brain (Bindocci et al, 2017;Chung et al, 2013;Martin, Bajo-Graneras, Moratalla, Perea, & Araque, 2015;Nimmerjahn & Bergles, 2015) and in disease (Bardehle et al, 2013;Delekate et al, 2014;John Lin et al, 2017;Yu et al, 2018). Future studies will need to implement such refined methods in relevant disease models, to study reactive astrocyte responses at the single-cell level.…”
Section: Which New Approaches and Tools Will Move The Field Forward?mentioning
confidence: 99%
“…This will occur when current experts in the field begin to adopt these techniques or when glial‐focused researchers turn their attention to stress disorders. There are now multiple tools available to control the activity of astrocytes in a precise spatial and temporal manner; this includes the chemogenetic and optogenetic manipulation of astrocytic signaling (Adamsky et al, ; Agulhon et al, ; Jones, Paniccia, Lebonville, Reissner, & Lysle, ; Mederos et al, ; Wang et al, ), as well as a novel approach to decrease endogenous astrocyte calcium activity by expressing a human plasma membrane calcium pump, which extrudes calcium from the cell (Yu et al, ). The use of these tools will greatly facilitate studies designed to better understand the role of astrocytes in the initiation, development, maintenance, or progression of stress disorders.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, mRNA for GAT-1 and for has been found in midbrain DA neurons and these GATs have been suggested but not confirmed to be located on striatal DA axons to support GABA co-storage and co-release (Tritsch et al, 2014). Ambient GABA tone on SPNs in dorsal striatum is limited by the activity of GAT-1 and GAT-3 (Kirmse et al, 2008(Kirmse et al, , 2009Santhakumar et al, 2010;Wójtowicz et al, 2013), and recent evidence indicates that dysregulation of GAT-3 on striatal astrocytes results in profound changes to SPN activity and striatal-dependent behavior (Yu et al, 2018).…”
Section: Introductionmentioning
confidence: 97%
“…Tonic inhibition by ambient GABA across the mammalian brain is usually limited by uptake by plasma membrane GABA transporters (GATs) (Brickley and Mody, 2012). There are two isoforms of the GAT in striatum: GAT-1 (Slc6a1), abundant in axons of GABAergic neurons (Augood et al, 1995;Durkin et al, 1995;Ng et al, 2000;Yasumi et al, 1997); and GAT-3 (Slc6a11), expressed moderately (Ficková et al, 1999;Ng et al, 2000;Yasumi et al, 1997) but observed particularly on astrocytes (Chai et al, 2017;Ng et al, 2000;Yu et al, 2018). Emerging transcriptomic data additionally indicate that striatal astrocytes express both GAT-3 and GAT-1 (Chai et al, 2017;Gokce et al, 2016;Zhang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%